Affairs of the heart: patients' personal constructions of a cardiac event and their effect on lifestyle change - EC McKibbin; KG Wilson (AOSIS, 2001)
The issue of why people do not always make appropriate lifestyle changes in response to a cardiac event has and continues to be of central importance to health practitioners. This paper addresses this issue from the perspective of the lived experience of persons who have suffered an acute myocardial infarction (AMI). The experiences of 10 persons admitted to the coronary care unit (CCU) of a South African clinic were richly described, making use of the grounded theory methodology. These descriptions were then used as a basis for the development of a contextualist theory of the experience of heart attacks. A central feature of the results was that the disease was mainly attributed to stress by the participants. This was in contrast to the explanations offered by the medical profession, who attribute this more to other modifiable risk factors such as smoking, high blood cholesterol, high blood pressure, and lack of exercise. This tension between lay and professional constructions of the aetiology of the condition is deemed to be of import in the recovery process. The paper further alludes to the goodness of fit which exists between the proposed grounded theory and the personal construct theory of George Kelly. The importance of personal constructions of the event is then used as the basis for a proposed intervention process aimed at addressing the difficulties AMI patients' experience in making and sustaining lifestyle changes.